2012
DOI: 10.1002/cphc.201100915
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Local Polarity of Alkylammonium Formate Ionic Liquids and Their Mixtures with Water by Using a Carbonyl Carotenoid

Abstract: Ultrafast transient absorption experiments have been carried out to determine the local polarity of three alkylammonium formate (AAF) protic ionic liquids (PILs), methlyammonium formate (MAF), ethylammonium formate (EAF), and n-butylammonium formate (BAF), by using 12'-apo-β-carotenoic-12'-acid (12'CA) as a molecular probe. MAF is more polar than methanol; EAF and BAF have polarities similar to ethanol and n-butanol, respectively. In general, the AAF PILs follow rather closely the correlation between the S(1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…The vibronic progression with a spacing of about 1250 cm –1 is typically assigned to a combination of two symmetric vibrational stretching modes C–C (1150 cm –1 ) and CC (1600 cm –1 ). , In acetonitrile this vibrational structure is considerably washed out, and the band is asymmetrically broadened toward larger wavelengths (see the inset in Figure ). A similar effect has been observed for other asymmetrically carbonyl-substituted carotenoids. ,, It is attributed to the dipolar character of S 0 leading to a broad distribution of solvation structures with different degree of stabilization of the negative partial charge on the carbonyl oxygen and consequently inhomogeneous broadening. In methanol, the spectral structure has even completely disappeared, and the red wing extends to even larger wavelengths.…”
Section: Resultssupporting
confidence: 68%
“…The vibronic progression with a spacing of about 1250 cm –1 is typically assigned to a combination of two symmetric vibrational stretching modes C–C (1150 cm –1 ) and CC (1600 cm –1 ). , In acetonitrile this vibrational structure is considerably washed out, and the band is asymmetrically broadened toward larger wavelengths (see the inset in Figure ). A similar effect has been observed for other asymmetrically carbonyl-substituted carotenoids. ,, It is attributed to the dipolar character of S 0 leading to a broad distribution of solvation structures with different degree of stabilization of the negative partial charge on the carbonyl oxygen and consequently inhomogeneous broadening. In methanol, the spectral structure has even completely disappeared, and the red wing extends to even larger wavelengths.…”
Section: Resultssupporting
confidence: 68%
“…It was determined that the polarity followed MAF > EAF > BAF, with MAF having a polarity greater than methanol, and EAF and BAF having polarities comparable to those of ethanol and butanol, respectively. 146 The polarity of EAF was shown to increase with added water, as expected because water is more polar than EAF. Molecular probes have also been used to give a measure of the acidity, using the Hammett parameter, of neat PILs, PIL−water solutions, and their precursor acids.…”
Section: Solvent Mixtures Containing Pilsmentioning
confidence: 78%
“…3 The three-dimensional hydrogen-bonded network structure with both the proton donor and acceptor sites is attractive for separation processes. 4−6 Several literature studies reported in the past used time-resolved IR spectroscopy, 7 friction force microscopy, 8 fluorescence probes, 9 electrochemical methods, 10 and molecular dynamics (MD) simulations 11 to describe the impact of cation symmetry and hydrophobicity on the structure and dynamics of PILs. 2,12 Alkylammonium formates are an interesting group of PILs in which the alkyl substitution at the ammonium head group leads to a variation of the physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…They are formed by a proton transfer from a Bronsted acid to a Bronsted base, , which can form extensive hydrogen-bonding networks because of their ability to donate and accept protons simultaneously . The three-dimensional hydrogen-bonded network structure with both the proton donor and acceptor sites is attractive for separation processes. Several literature studies reported in the past used time-resolved IR spectroscopy, friction force microscopy, fluorescence probes, electrochemical methods, and molecular dynamics (MD) simulations to describe the impact of cation symmetry and hydrophobicity on the structure and dynamics of PILs. , Alkylammonium formates are an interesting group of PILs in which the alkyl substitution at the ammonium head group leads to a variation of the physicochemical properties. , Alkylammonium ions act as alternate solvents governing the protein structure, stability, and enzyme catalysis. , PILs based on the alkylammonium cations can be used as a mobile phase modifier replacing organic solvents in reversed-phase liquid chromatography. , The detection of alkylammonium ions in the dopamine neurotransmitters helps identify the reason behind Parkinson’s disease caused by the malfunctioning of dopamine-responsive neurons. , To fully exploit the potential applicability of PILs, it is necessary to know their basic molecular-level structure along with a detailed understanding of their ultrafast dynamical properties. While spectral investigations unveil the unique architecture of ionic environments, spectroscopic calculations predict the dynamical response in complicated ionic liquids (ILs). , Methylammonium formate (MAF) ionic liquid, mainly studied here, belongs to this category of PIL.…”
Section: Introductionmentioning
confidence: 99%